Age and gender patterns in COVID-19: Insights from a Regional COVID-19 testing center - Adam M. Franks; Danny Holbert; Justin West; Eric Trent; John Parker; Courtney Wellman; Alperen Korkmaz; Tammy Bannister (Journal of Family Medicine and Primary Care)
Introduction: Asymptomatic and targeted testing are critical for mitigating the spread of COVID-19. Understanding testing demand is crucial for efficient personnel and resource management. The study analyzes testing data to uncover factors influencing testing demand. Methods: Testing and infection data were consolidated into weekly intervals, grouped into pediatric (0–17.99 years), adult (18–64.99 years), and geriatric (65 + years) cohorts, and plotted longitudinally. Changes in overall testing, infectivity, and age-appropriate vaccination availability were analyzed between groups. Simple paired t-table Chi-square testing calculated significance (P < 0.05). Results: Of 69,612 COVID-19 tests, 13,447 (19.3%) were pediatric, 48,084 (69.1%) were adult, and 8,081 (11.6%) were geriatric. A high correlation was seen for pediatric vs. adult (0.73; P < 0.05), pediatric vs. geriatric (0.62; P < 0.05), and adult vs geriatric (0.93; P < 0.05). Pediatric testing differed from adult and geriatric testing during peak overall testing (both P < 0.001) and infectivity (P < 0.001 and 0.002, respectively). Pediatric testing increased 1.7-fold (P < 0.001) following immunization availability. Gender differences were seen between all groups with pediatrics being less female (P < 0.001). Changes in overall testing, infectivity, and immunization availability didn’t change gender ratios significantly within or between groups. Pediatric testing was less female for peak overall testing (P < 0.001) and infectivity (P = 0.032). Conclusion: Pediatric testing was more associated with times of high infectivity and did not benefit from vaccination availability. Gender differences occurred between groups, but influences did not change gender ratios within each group. Understanding factors altering COVID-19 testing patterns can inform management of resource and personnel allocation for the next public health crisis.